Parentesco Jurúna - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1970)
The Jurúna, a tupian speaking people migrated from the Lower to the Upper Xingu River. Nowadays they have a single village with 58 persons and are settled at the boundaries of the Diauarum Post (Parque Nacional do Xingu). This paper focuses the Jurúna kinship because of its basic implication on the present organization of the social life. The traditional kinship rules and marriage regulations still survive in their totality, adapted to the present day situation define by a high degree of depopulation. The use of Brazilian kinship terms isn´t unfrequent but the basic refrence is yet conditioned by the Jurúna terminology. The same occurs with the expectations and the atributions of rights and duties. The essential feature of the Jurúna system are: - bilaterality. - bifurcate-merging terminology on the first ascending and first descending generation. - Iroquois terminology on ego´s generation. - merged terminology on the second ascending and second descending generations. With respect to the marriages, arrangements were made to cope with the demographic situation.
Keywords: Índios Jurúna; Relações de parentesco; Parque Nacional do Xingu; Rio Xingu (MT)